Expectation of the Communication Mechanism and its Gap in Public Administration: Approaches to Communication between Local Government and Public - Aryal, Bhagwan; Poudel, Bhumidatta; Karki, Jagadish; Bhattarai, Nawaraj; Bhandari, Sriprasad (Nepal Journal of Multidisciplinary Research, 2024)
Background: The gap in public administration is exacerbated by ineffective communication, limiting accessibility, and hindering underrepresented groups. Conventional methods like press releases and meetings may not always effectively involve the public. Innovative participatory communication techniques can improve governance quality, strengthen constituent ties, and increase openness. This study examines local government communication methods with the public, revealing expectations for transparency, openness, and participation, identifying communication gaps, and exploring effective strategies for public-government communication. Methods: The study utilized a mixed-methods approach, involving 315 citizens, plus 6 staff, elected members, and local intellectuals in Ward No. 10 of Budhanilkantha municipality, using surveys and interviews. Results: While digital technology usage is moderate to high, fulfillment of public expectations for local government communication mechanisms was negative, with over 60% rating them negatively and 77.4% believing they were political. A majority of respondents (76.2%) received information from local governments or ward offices through social media, followed by man-to-man communication (54.6%) and mass media (52.7%). Ineffective communication can hinder citizen participation and challenge older adults and uneducated individuals. Key elements of successful communication include accuracy, efficiency, resourcefulness, immediate news flow, and technology use. Public recommendations include online feedback platforms, local government employees, and community outreach programs. Conclusion: The public expects open communication, digital tools, transparency, and freedom of politics. To foster trust and engage the public, frequent meetings, online discussions, local personnel recruiting, community outreach, trust development, and customized interaction are necessary. Novelty: The study could provide insights into a new approach to public-local government communication, emphasizing transparency, community concerns, and collaboration.